PENGARUH PENGHARGAAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. ANARA TRISAKTI MEDIKA JAKARTA TIMUR - Fahri Ibnu Rezani; Ella Siti Chaeriah (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
This study aims to examine the effect of rewards and work motivation on employee performance. This research was conducted at a medical equipment company in East Jakarta. Data collection was carried out using a questionnaire to respondents. This research was tested with validity and reliability test, classic assumption test, and simple and multiple linear regression analysis test. The results of this study partially giving awards a positive and significant effect on the performance of employees of PT. Anara Trisakti Medika East Jakarta, work motivation has a positive and significant effect on the performance of the employees of PT. Anara Trisakti Medika East Jakarta, and giving awards and work motivation together have a positive and significant effect on the performance of the employees of PT. Anara Trisakti Medika East Jakarta.